Worse recovery from acute attacks and faster disability accumulation highlights the unmet need for improved treatment in patients with late-onset neuromyelitis optica spectrum disorders (COPTER-LO study) - Julian Reza Kretschmer; Daria Tkachenko; Tania Kümpfel; Joachim Havla; Daniel Engels; Friedemann Paul; Friedemann Paul; Patrick Schindler; Patrick Schindler; Judith Bellmann-Strobl; Judith Bellmann-Strobl; Achim Berthele; et al. (Frontiers in Immunology)
ObjectiveThis study analyzed clinical characteristics, attack recovery and long-term disability accumulation in late-onset (LO ≥ 50 years at onset) versus early-onset (EO < 50 years) NMOSD.MethodsThis multicenter cohort study included demographic and clinical data from 446 NMOSD patients collected from 35 German Neuromyelitis Optica Study Group (NEMOS) centers. Time to disability milestones was estimated through Kaplan-Meier analysis and Cox proportional hazard regression models adjusted for sex, year of onset, immunotherapy exposure and antibody status. Generalized estimating equations (GEE) were used to compare attack outcomes.ResultsOf the 446 NMOSD patients analyzed (83.4% female, 85.4% AQP4-IgG-positive, median age at disease onset = 43 years), 153 had a late-onset (34.3%). AQP4-IgG+ prevalence was higher in LO- than in EO-NMOSD (94.1% vs. 80.9%, p<0.001). Optic neuritis at onset was more frequent in EO-NMOSD (27.4% vs. 42.6%, p<0.002), whereas myelitis was more common in LO-NMOSD (58.4% vs. 37.9%, p<0.001). Both groups had similar annualized attack rates (AAR, 0.51 vs. 0.54, p=0.352), but attack recovery was poorer (complete remission in 15.6% vs. 27.4%, p<0.001) and relapse-associated worsening (RAW) was higher in LO-NMOSD (RAW: 3 vs. 0.5, p<0.001). Long-term immunotherapy use was comparable. LO-NMOSD exhibited faster progression to disability endpoints (EDSS 4: HR = 2.64, 95% CI=1.81–3.84).InterpretationLO-NMOSD patients presented more often with myelitis, experienced worse attack outcomes and faster disability accumulation, despite comparable AAR, acute attack treatment and long-term treatment regimens. Accordingly, therapeutic strategies for attack and prophylactic treatment in LO-NMOSD have to be improved.